MicroRNA control in the development of systemic autoimmunity - Hu, Ruozhen (BioMed Central, 2013)
Mammalian immune responses are intended to eradicate microbial pathogens and thus protect individuals from the harmful effects of such infections. However, unresolved inflammation can be devastating to the host and cause tissue damage and organ malfunction. Immune responses can even mistakenly target self-antigens and mediate autoimmune inflammation. Consequently, a variety of cellular and molecular mechanisms have evolved to control the inflammatory responses, and many of these safeguards or triggers are perturbed in the setting of autoimmunity. In this review, we discuss the emerging roles of cellular non-coding RNAs, and in particular microRNAs (miRNAs), in the regulation of autoimmune inflammation. How miRNAs function to impact the onset, magnitude, and resolution of inflammatory responses and recent observations regarding links between miRNAs and specific autoimmune disorders will be addressed. Finally, the diagnostic and therapeutic relevance of miRNAs involved in autoimmunity will be considered. It is clear that, taken together, mammalian miRNAs are integral to the pathogenesis of mammalian autoimmune diseases and may be effective targets of next-generation therapeutics aimed at eradicating tissue inflammation.